First-principles study of the structure, magnetism, and electronic properties of the all-Heusler alloy Co2MnGe/CoTiMnGe(100) heterojunction - He, Jianqiao; Huang, Haishen; Wu, Bo; Shen, Guangxian; Zhou, Tingyan; Gu, Yuxin; Wen, Lin; Zhang, Qingqing (Frontiers in Chemistry, 2024)
Based on first-principles calculations in the density functional theory, we systematically investigated the possible interface structure, magnetism, and electronic properties of the all-Heusler alloy Co2MnGe/CoTiMnGe(100) heterojunction. The calculation indicated that the Co2MnGe Heusler alloy is a half-metal with a magnetic moment of 4.97 μB. CoTiMnGe is a narrow-band gap semiconductor and may act as an ultra-sensitive photocatalyst. We cannot find an “ideal” spin-polarization of 100% in CoCo termination and MnGe termination. Due to the interface interaction, the direct magnetic hybridization or indirect RKKY exchange will be weakened, leading to an increase in the atomic magnetic moment of the interfacial layer. For eight possible heterojunction structures, the half-metallic gaps in the Co2MnGe bulk have been destroyed by the inevitable interface states. The spin-polarization value of 94.31% in the CoCo-TiGe-B heterojunction revealed that it is the most stable structure. It is feasible to search for high-performance magnetic tunnel junction by artificially constructing suitable all-Heusler alloy heterojunctions.